2017
DOI: 10.1113/ep086249
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cerebral blood flow and metabolism during exercise

Abstract: What is the topic of this review? The manuscript collectively combines the experimental observations from >100 publications focusing on the regulation of cerebral blood flow and metabolism during exercise from 1945 to the present day. What advances does it highlight? This article highlights the importance of traditional and historical assessments of cerebral blood flow and metabolism during exercise, as well as traditional and new insights into the complex factors involved in the integrative regulation of brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
241
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(257 citation statements)
references
References 117 publications
(357 reference statements)
13
241
2
1
Order By: Relevance
“…The latter finding could be derived to the fact that the MICT condition was calculated to occur at roughly 50%-60% VO2max, which was insufficient to reach significance from baseline values, but was sufficient to elicit the expected elevations to CBV (Table 1). Collectively, the physiological changes seen during the three conditions employed in this investigation are in agreement with previous work that have examined physiological measurements during exercise Smith & Ainslie, 2017). Furthermore, individuals are able to maintain exercise up to an intensity of roughly 60%-70% of their VO 2max for prolonged durations as this intensity is typically below the anaerobic threshold (Mateika & Duffin, 1995).…”
Section: Potential Mechanisms Underlying the Alterations Between Exsupporting
confidence: 90%
See 2 more Smart Citations
“…The latter finding could be derived to the fact that the MICT condition was calculated to occur at roughly 50%-60% VO2max, which was insufficient to reach significance from baseline values, but was sufficient to elicit the expected elevations to CBV (Table 1). Collectively, the physiological changes seen during the three conditions employed in this investigation are in agreement with previous work that have examined physiological measurements during exercise Smith & Ainslie, 2017). Furthermore, individuals are able to maintain exercise up to an intensity of roughly 60%-70% of their VO 2max for prolonged durations as this intensity is typically below the anaerobic threshold (Mateika & Duffin, 1995).…”
Section: Potential Mechanisms Underlying the Alterations Between Exsupporting
confidence: 90%
“…Koch et al (2005) also observed a decrease in phase following dynamic resistance exercise during the early recovery period (80 s). The change in phase angle across the cardiac cycle in the current study following MICT exercise may be attributed to more compliancy within the dilated vasculature, known to occur during moderate exercise Smith & Ainslie, 2017). Such dilation likely occurred throughout the entirety of the MICT protocol, due to hyperpnea-induced vasodilation, which potential led to more compliant vasculature.…”
Section: Comparison With Previous Studiesmentioning
confidence: 75%
See 1 more Smart Citation
“…The cerebral metabolic response to hyperthermia can perhaps be gleaned from exercising data, but again the findings are inconsistent (see review by Smith et al . ). For example, Nybo et al .…”
Section: Introductionmentioning
confidence: 97%
“…7 The increase in MCA V mean during low to moderate exercise is attributed, at least in part, to the initial increase in arterial carbon dioxide tension (PaCO 2 ) in response to exercise metabolism. Yet, as exercise intensity progresses, MCA V mean is either plateuing or reduced toward the resting value, dependent on the magnitude of hyperventilation-induced hypocapnia, 3,4,8 that may reduce PaCO 2 to as low as ~29 mmHg. 9 A similar response pattern is described for the NIRS-determined frontal lobe oxygenation (ScO 2 ) with an increase during low intensity exercise and then a gradual decrease when exercise intensity approaches a maximal level and exercise-induced hypocapnia develops.…”
Section: Introductionmentioning
confidence: 99%